Signet ring cell-like diffuse large B-cell lymphoma involving the breast: a case report - Lu Zhang; Qinqin Min; Jiaxin Bi; Xuewen Yu; Yingying Liang; Mumin Shao (BMC Women's Health, 2023)
Abstract Background Diffuse large B-cell lymphoma (DLBCL) with signet ring cell components is extremely rare. Here, we present a case of DLBCL with signet ring cell components involving the breast, which can be easily confused with invasive lobular carcinoma of the breast or metastatic signet ring cell carcinoma of gastrointestinal origin. Case presentation A 66-year-old woman presented with a painless mass in her left breast. Enhanced magnetic resonance imaging (MRI) of the breast revealed a 42 × 29 × 28 mm mass in the left breast. Histological examination revealed a diffuse or scattered arrangement of round cells mixed with signet ring-like cells. Immunohistochemically, the neoplastic cells were positive for PAX-5, CD79a, CD20, Bcl-6, and MUM-1 but and negative for cytokeratin, ER, PR, E-cadherin, and P120. The Ki-67 proliferation index was approximately 70%. Fluorescence in situ hybridisation (FISH) demonstrated non-rearrangement of Bcl-2, Bcl-6, and c-MYC genes. Immunohistochemistry and FISH examination confirmed the diagnosis of DLBCL. Subsequently, immunofluorescence showed both IgM and IgG deposits in the signet ring-like lymphocytes. After confirming the diagnosis, the patient received four courses of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) chemotherapy in a specialist hospital and achieved partial remission; however, she unfortunately died of secondary pneumocystis pneumonia infection 3 months later. Conclusion Malignant lymphoma with signet ring cell morphology is quite uncommon, and this variant can be a diagnostic pitfall. We emphasise that pathologists should consider lymphoma in the differential diagnosis of malignant breast tumours.